2022
DOI: 10.1038/s41598-022-05784-w
|View full text |Cite
|
Sign up to set email alerts
|

Sample-efficient parameter exploration of the powder film drying process using experiment-based Bayesian optimization

Abstract: Parameter optimization is a long-standing challenge in various production processes. Particularly, powder film forming processes entail multiscale and multiphysical phenomena, each of which is usually controlled by a combination of several parameters. Therefore, it is difficult to optimize the parameters either by numerical-model-based analysis or by “brute force” experiment-based exploration. In this study, we focus on a Bayesian optimization method that has led to breakthroughs in materials informatics. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…This would enable humans to understand these hazardous odors and dramatically reduce the number of accidents based on hazardous odors such as natural gas leaked from pipelines 5 and volcanic gases. 6 To establish an automated odor-blending system, we need to develop three elements: an olfactory sensor [7][8][9][10][11][12][13] to replace the human sense of odors, blackbox optimization [14][15][16] to determine the amount of blending, and a robotic system [17][18][19][20][21][22][23][24][25] to perform actual blending of samples.…”
Section: Introductionmentioning
confidence: 99%
“…This would enable humans to understand these hazardous odors and dramatically reduce the number of accidents based on hazardous odors such as natural gas leaked from pipelines 5 and volcanic gases. 6 To establish an automated odor-blending system, we need to develop three elements: an olfactory sensor [7][8][9][10][11][12][13] to replace the human sense of odors, blackbox optimization [14][15][16] to determine the amount of blending, and a robotic system [17][18][19][20][21][22][23][24][25] to perform actual blending of samples.…”
Section: Introductionmentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 successfully applied BO to the identification of processing conditions that minimized the formation of defects in powder films while carrying out a limited number of experiments. 31 Given that BO is predicated on the acquisition of experimental data, numerous experiments are typically required for method validation and so it is advantageous to employ experimental techniques capable of generating abundant, highly reproducible data. In this context, high-throughput methods for materials exploration [32][33][34][35] and analysis [36][37][38] are increasingly being integrated with machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Nugraha et al 55 demonstrated that BO can efficiently aid in designing experiments to discover the optimal composition of metal precursors, yielding mesoporous ternary metal PtPdAu alloys with enhanced electrocatalytic activity in methanol oxidation. Nagai et al 56 applied BO to the drying process of catalyst inks for polymer electrolyte fuel cells to determine optimal drying conditions with a small number of trials. Okazawa et al 19 used a combination of BO and DFT calculations to find the optimal binary alloy catalyst for the nitrogen activation reaction.…”
Section: Introductionmentioning
confidence: 99%